SISTEM PEMERINTAHAN PADA MASA KHULAFAURASYIDDIN: NILAI-NILAI AKHLAK KEPEMIMPINAN DAN RELEVANSINYA BAGI KEHIDUPAN MODERN - Lidhah Sekar Mulatsih; Intan Nur Azizah (El-Hikmah: Jurnal Ilmu Dakwah dan Komunikasi, 2026)
This study examines the Islamic governance system during the Khulafaurrasyidin era (632–661 CE), focusing on the moral (akhlak) values embedded in the leadership of Abu Bakar Ash-Shiddiq, Umar bin Khattab, Utsman bin Affan, and Ali bin Abi Thalib. Using a qualitative library research method, this study analyzes primary sources including the Qur'an, Hadith, and classical Islamic historical texts, as well as secondary sources from relevant scientific journals and books. The findings reveal that the Khulafaurrasyidin governance model was built on five core moral values: amanah (trustworthiness), adl (justice), syura (deliberation), zuhud (non-attachment to worldly power), and tawadhu (humility). Each caliph exemplified these values distinctly Abu Bakar through his truthfulness and firmness, Umar through his strict justice and administrative innovation, Utsman through his generosity and textual preservation, and Ali through his courage and profound knowledge. These moral values are not merely historical artifacts but remain deeply relevant to contemporary Islamic leadership challenges. This study concludes that the Khulafaurrasyidin model offers a comprehensive ethical framework for modern Muslim leaders, grounded in both divine revelation and prophetic tradition.